Trabalho do formador de professores para a educação profissional - Perez, Deivis [UNESP] (My University, 2014)
This article presents research that examined work of a teacher trainer for professional education, which aimed to study the work of these professional instruments , the design of pedagogical mediation underlying the prescriptive texts of the work and the theoretical-methodological arrays deployed in labor activity . The theoretical framework was Clinical Activity , strand of Work Psychology . We adopt a simple self-confrontation for data collection , combining interviews , document analysis, and video recording of the work . Were the volunteer coordinator and three trainers course in São Paulo educational institution. The results showed that the work of trainers activity is directed to others , using concrete and intangible instruments . Prescriptive texts suggest the use of cognitive education approach , but in the effective action of the trainers was adopted cultural-historical perspective of human development . At the end there are the limitations of this research and indicates the need for further scientific research on the subject.

Este artigo apresenta pesquisa sobre o trabalho do formador de professores para educação profissional, que objetivou examinar os instrumentos laborais destes profissionais, a concepção de mediação pedagógica subjacente aos textos prescritivos do trabalho e as matrizes teórico-metodológicas mobilizadas na atividade laboral. O aporte teórico foi a Clínica da Atividade, vertente da Psicologia do Trabalho. Adotou-se a autoconfrontação simples para recolha dos dados, que articula entrevista, observação, análise documental e registro em vídeo do trabalho. Foram voluntários o coordenador e três formadores de curso de instituição educacional paulista. Os resultados apontaram que o trabalho dos formadores é atividade dirigida para outras pessoas, com uso de instrumentos concretos e imateriais. Os textos prescritivos sugerem a utilização da abordagem cognitivista de educação, mas na ação efetiva dos formadores adotouse perspectiva histórico-cultural de desenvolvimento humano. Ao final há as limitações desta pesquisa e sinaliza-se a necessidade de produção ulterior de estudos sobre a temática.
Work trainers of teachers for professional education
Keywords: Work psychology; Professional education; Trainer’s work; Psicologia do trabalho; Educação profissional; Trabalho do formador